Redesigning Innovative Governance of Islamic Educational Organizations to Address the Complexity of Global Dynamics - Abd Wahed; Abu Siri (Khazanah: Journal of Islamic Education and Science, 2025)
This study was motivated by the increasing complexity of global dynamics affecting the governance of Islamic educational institutions, including accelerated digital transformation, demands for public accountability, and international academic quality competition. Many institutions have undertaken administrative reforms; however, they have not fully developed innovative governance models that integrate organizational values with global strategic orientation. This study aimed to analyze an innovative redesign model of governance in Islamic educational organizations and its relevance in strengthening institutional competitiveness. A descriptive qualitative approach was employed using a Systematic Literature Review design of scholarly articles published between 2016 and 2025, retrieved from the Scopus, Google Scholar, and Sinta databases. Data were analyzed through content analysis and thematic analysis to systematically synthesize cross-study findings. The results indicated that the integration of governance structural reform, institutionalization of innovation culture, and internalization of Islamic values within managerial systems contributed to enhanced organizational adaptability, institutional legitimacy, and global competitiveness. This study offered theoretical contributions through a value-based innovative governance model and practical contributions in the form of an operational framework for institutional transformation.